Teacher Educators in South Africa: Critically Examining Structural Inequalities and Sustainability through a Pedagogy of Discomfort - Phuthi, Brita (Education as Change, 2025)
Education is seen as a key vehicle to achieve the Sustainable Development Goals (SDGs) by 2030. Teacher educators play a pivotal role in training teachers and UNESCO advocates that Education for Sustainable Development (ESD) is mainstreamed through teacher education to contribute towards achieving the SDGs. For education to contribute to a more sustainable future, a focus on root causes to inequality in society, such as structural racism, and how to dismantle these structures, should be central. Drawing on empirical data from reflective dialogue interviews with 10 teacher educators at three universities in South Africa, this article explores their pedagogical approaches to include the concept of structural racism in their praxis. Their strategies for critically examining structural racism, in the context of South Africa, are considered in relation to relevant literature on critical pedagogy. The article further reflects on how this work relates to ESD and its aim for education to contribute to transformation to a more equal and just world. Based on the empirical work, the article argues that pedagogies of discomfort (and love) are important approaches for education to contribute to societal transformation through critically examining the root causes of inequalities and injustices.